Pengaruh Strategi Promosi Melalui Social Media Terhadap Keputusan Pembelian : Studi Kasus Pada Rumah Makan Seblak Nampol Di Masa Covid-19 - Adikah Soekarman; Roswaty Roswaty; Meilin Veronica (Training & Research Institute - Jeramba Ilmu Sukses, 2021)
This study aims to analyze the effect of promotional strategies through social media on purchasing decisions (a case study of the Seblak Nampol restaurant during the Covid-19 period). The data used in this study were obtained from interviews and questionnaires filled out by 86 respondents. The research method used is simple linear regression analysis. The research results prove that promotion through social media has a significant positive effect on purchasing decisions. This research is expected to become additional literature on the topic of promotion through social media and help companies better understand consumer purchasing decisions